10.6k views
1 vote
Multiply the polynomials (4x^2+x+7)(8x-5)

2 Answers

4 votes

♫ - - - - - - - - - - - - - - - ~Hello There!~ - - - - - - - - - - - - - - - ♫

➷Multiply everything together

(4x2+x+7)(8x−5)

=(4x2+x+7)(8x+−5)

=(4x2)(8x)+(4x2)(−5)+(x)(8x)+(x)(−5)+(7)(8x)+(7)(−5)

=32x3−20x2+8x2−5x+56x−35

=32x3−12x2+51x−35

Final answer:

32x3−12x2+51x−35

➶ Hope This Helps You!

➶ Good Luck (:

➶ Have A Great Day ^-^

TROLLER

User Jon Combe
by
6.2k points
4 votes

Answer: SIMPLIFY TERMS === 32X^3-12X^2+51X=35

Explanation:

(4x2+x+7)(8x−5)

Expand (4x2+x+7)(8x−5)

by multiplying each term in the first expression by each term in the second expression.

4x2(8x)+4x2⋅−5+(x(8x)+x⋅−5)+(7(8x)+7⋅−5)

Simplify terms.

Tap for more steps...

32x3−12x2+51x−35

User RobinDunn
by
6.1k points